The role of immunohistochemistry in the Muir-Torre Syndrome - Cláudia Marina Puga Barbosa Oliveira; Jullyene Gomes de Campos; Maiko Ramacos Maia; Larissa Eva dos Santos Lobo; Fábio Francesconi do Valle (Sociedade Brasileira de Dermatologia, 2015)
AbstractMuir-Torre Syndrome is defined by the coexistence of sebaceous skin tumors and internal malignancies. Mutations in the DNA mismatch repair genes are found in the inherited form of the disease, resulting in the absence of crucial enzymes involved with DNA replication process. This case describes a patient with sebaceous adenoma and colorectal carcinoma, meeting the criteria for Muir-Torre Syndrome. The immunohistochemical analysis of the skin lesion was an important tool to confirm the diagnosis, as it revealed nuclear negativity for MSH2 and MSH6.